Genetic variability of Hepatitis B virus - Bajunaid, Huda Ahmad (2013)
We detected HBV-DNA in two out of 15 (13.3%) archival liver biopsies from Saudi HCC patients. Our real-time quantitative assay of HBV by SYBR green was more accurate and has detection range from 102 to 1010 copies/ml. The melting temperature varied 80.5 - 81.7 oC in different genotypes. Mean HBV DNA level was significantly higher in UK than Saudi hepatitis B patients at 5.09 (95% CI 1.43-8.75) and 4.52 (95% CI 0.14-8.90) log10 copies/ml, respectively (p: 0.007). Mean HBV DNA in patients with HBeAg was higher at 7.18 and 6.44 log10 copies/ml in UK and Saudi patients, respectively. HBV genotypes A, B, C and D were mostly detected in UK patients, A and D in Saudi patients. In UK patients, genotypes C and D showed higher mean HBV DNA than genotypes A or B. Saudi patients had higher mean HBV DNA in genotypes D than genotypes A or B. Within genotype D, UK patients had even higher HBV DNA levels than Saudi patients at 6.10 and 5.10 log10 IU/ml, respectively. All UK HBV genotype A had subgenotype Ae, genotype B had subgenotype Ba, and genotype C subgenotype C1 (Cs). HBV detected in Saudi Samples had HBV subgenotype D1, while UK had subgenotype D2 mostly in Asian patients.